The systemic marginalisation of long-term casualised researchers in UK higher education - Menard, Cecile B. (Frontiers in Sociology, 2025)
While casualisation of academic labour has garnered significant scholarly attention, much has focused on “early career researchers” (ECRs), an all-encompassing term that masks the long-term precarity many academics face. This study challenges that narrative by centering long-term researchers (LTRs)—defined as those in casualised research roles for 8 years or more—who are overlooked in policy and discourse. Drawing on a survey of LTRs (n = 179) in UK universities integrating qualitative and quantitative data, this study examines their career trajectories, academic contributions and barriers to progression. The study highlights systemic and structural mechanisms within universities and funding bodies that marginalise and invisibilise LTRs, such as exclusionary career frameworks, exploitative hierarchies and lack of mentoring, as well as the normalisation of precarity as an academic “rite of passage.” The findings expose a disconnect between the value LTRs bring—e.g. when securing grants, sustaining research continuity, teaching and supervising—and the lack of recognition or progression routes available to them. It shows how widespread bullying and discrimination at the intersection of ageism, gender discrimination and caring responsibilities—experienced by 40% of participants—combined with trajectorism and the illusion of meritocracy entrench inequities in HE. This study calls for actionable policy interventions, such as formal recognition of LTRs as a distinct category, greater transparency on the true extent of casualisation and career opportunities that prioritise intellectual contributions over arbitrary employment status. Such sector-wide structural reforms are imperative to dismantle the very systems that enable and profit from the exploitation of precarious academic labour and to put an end to long-term insecurity in HE.